Botanical Origin and Extraction Methods of Philippine Stingless Bee (Tetragonula biroi Friese) Pollen and its Food Functionality: Phenolic and Flavonoid Content and Antioxidant Activity: Philippine Stingless Bee Pollen Food Functionality - Deocaris, Custer; Salcedo, Fernando; Sullivan, Carly; Micor, Jose Rene; Alinsug, Malona; Mojica, Elmer-Rico E (Journal of Tropical Life Science, 2024)
With its high nutritional and bioactive content, bee pollen is recognized as a functional food. However, its composition is highly dependent on a range of factors, such as geographical location. In this research, we used DPPH to determine the antioxidant activity of several stingless bee (Tetragonula biroi) pollen samples sourced from five different areas in the Philippines and compare their phenolic and flavonoid content. Additionally, we compared two extraction methods: maceration (or soaking of samples) for three days and sonication for 30 minutes. Interestingly, our findings show that the phenolic content of bee pollen is weakly associated with antioxidant activity, indicating that other bioactive chemicals may play a more significant part in the antioxidant characteristics of bee pollen. Antioxidant properties based on the DPPH assay of pollen harvested from Calamba are higher compared to other samples from different geographic areas, i.e., Quezon Province, Sorsogon, Laguna, and Albay. When compared to the maceration approach, extracts generated from the sonication process had lower antioxidant activity. These findings suggest that Philippine stingless bee pollen is a potential source of bioactive compounds, and the choice of extraction method and geographic source are significant factors affecting its antioxidant activity.